Local delivery of tetracycline group of drugs as adjuncts to mechanical debridement in peri-implantitis: a systematic review and meta-analysis - Banu, Sunaina; G., Pratibha; H.R., Rajeshwari; N., Ravishankar (Journal of Stomatology, 2021)
Peri-implantitis is associated with bone loss around a dental implant. Apart from mechanical factors, microbial etiology with gram-negative anaerobic infection is implied. The condition can have a favorable prognosis with timely control of infection, implant surface detoxification, and bone regeneration. Further, since it is site-specific, there is a potential for targeted form of antimicrobial therapy. Tetracycline has been the conventional choice for local delivery agents. The present review systematically assessed the randomized and controlled clinical trials, evaluating the efficacy of local delivery of the tetracycline group of drugs adjunctive to non-surgical peri-implant debridement in the management of mild to moderate cases of peri-implantitis. We explored databases of PubMed, Cochrane Library, and Scopus electronically to include research papers published in English till the end of May 2019. In the first stage of assortment, we screened titles and abstracts and in the second stage, the selected papers were evaluated independently by three reviewers. From the initial search, we included 810 related titles and abstracts. Around seven articles were selected for rigorous evaluation after screening. Finally, only three papers met the inclusion criteria and were selected for the final review and meta-analysis. Based on our analysis, we found scant evidence to support the tetracycline group of drugs in mild to moderate peri-implantitis. Research in this area is limited and warrants further investigation through longitudinal, randomized, and controlled clinical trials.